2011
DOI: 10.1111/j.1468-3083.2011.04004.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative epidemiological study of non‐melanoma skin cancer between Spanish and north and central European residents on the Costa del Sol

Abstract: Persons from the north and centre of Europe living on the Costa del Sol present a different pattern of NMSC to the local Spanish population and usually require a less invasive therapeutic approach. These findings highlight the need to define prevention and treatment policies for NMSC according to the characteristics of each particular population. This would help reduce not only the frequency but also the associated morbimortality of this disease, particularly in high-risk populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 33 publications
2
14
0
1
Order By: Relevance
“…12 Moreover, studies have shown that taking photographs under Wood light, showing patients their light-induced skin damage, and explaining the significance of the damage is an effective way to improve sun protection behaviors, even in the long term. 25,26 The results confirmed that golfers (in particular) and golf course workers (especially those who work outdoors) were groups at risk of developing skin cancer because of their intrinsic risk factors, the fact that they have fair or very fair skin (especially the golfers, many of whom were from central or northern Europe), 15 and their considerable history of skin cancer---both family history and, more importantly, personal history (especially in golfers). Golfers and golf course workers also faced risks associated with their sun exposure habits.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…12 Moreover, studies have shown that taking photographs under Wood light, showing patients their light-induced skin damage, and explaining the significance of the damage is an effective way to improve sun protection behaviors, even in the long term. 25,26 The results confirmed that golfers (in particular) and golf course workers (especially those who work outdoors) were groups at risk of developing skin cancer because of their intrinsic risk factors, the fact that they have fair or very fair skin (especially the golfers, many of whom were from central or northern Europe), 15 and their considerable history of skin cancer---both family history and, more importantly, personal history (especially in golfers). Golfers and golf course workers also faced risks associated with their sun exposure habits.…”
Section: Discussionsupporting
confidence: 77%
“…10,12 Spain's Costa del Sol has a higher concentration of golf courses than any other region of Europe---hence its nickname, ''Costa del Golf''---and it is also home to many foreign-born individuals, predominantly from northern and central Europe, 13 who are attracted by the region's more than 300 days of sun per year. 14 These residents have been identified as a group at risk of developing skin cancer and their high prevalence of cutaneous neoplasms 15 is fundamentally associated with recreational sun exposure, often golf-related. Likewise, many tourists---especially those from outside of Spain, in particular northern and central Europeans---are attracted to the region's sun and beaches, but also in many cases to its golf courses.…”
Section: Introductionmentioning
confidence: 99%
“…The level of solar irradiation is very high in this area, where the UV index can reach 10 or 11 in the summer months . Skin cancer is a significant health problem in the Costa del Sol, and skin cancer prevention campaigns targeting beachgoers have been developed . The aim of this study was to describe the prevalence of sunburn among beachgoers in this area and to identify risk factors that will help to inform future educational interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Estos ya fueron identificados como grupo de riesgo de desarrollo de cáncer de piel, presentando una alta prevalencia de neoplasias cutáneas 15 relacionada fundamentalmente a una exposición solar recreativa, frecuentemente relacionada con el golf. Igualmente muchos turistas (sobre todo extranjeros que también suelen proceder del Norte y Centro de Europa) acuden atraídos por el sol y la playa, pero también en muchos casos por el golf.…”
Section: Introductionunclassified